2023
DOI: 10.1073/pnas.2218959120
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of nanobodies specific for BCL11A

Abstract: Transcription factors (TFs) control numerous genes that are directly relevant to many human disorders. However, developing specific reagents targeting TFs within intact cells is challenging due to the presence of highly disordered regions within these proteins. Intracellular antibodies offer opportunities to probe protein function and validate therapeutic targets. Here, we describe the optimization of nanobodies specific for BCL11A, a validated target for the treatment of hemoglobin disorders. We obtained firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…We found that predicted brain ages generated by a densely connected neural network using 3 distinct sets of neuroimaging features (FW-corrected dMRI, T1-weighted MRI, combined FW+T1) all showed high correlation with actual age in baseline CU participants, which confirms findings from previous literature that have accurately predicted chronological age of healthy adults using neuroimaging-derived measures with machine learning approaches including deep learning 11,12,17,2629 . Importantly, the top-contributing neuroimaging features identified for each model ( Figure 2 ) provide biological interpretability as they include brain regions that have been associated with both normal aging and AD neuropathology.…”
Section: Discussionsupporting
confidence: 86%
“…We found that predicted brain ages generated by a densely connected neural network using 3 distinct sets of neuroimaging features (FW-corrected dMRI, T1-weighted MRI, combined FW+T1) all showed high correlation with actual age in baseline CU participants, which confirms findings from previous literature that have accurately predicted chronological age of healthy adults using neuroimaging-derived measures with machine learning approaches including deep learning 11,12,17,2629 . Importantly, the top-contributing neuroimaging features identified for each model ( Figure 2 ) provide biological interpretability as they include brain regions that have been associated with both normal aging and AD neuropathology.…”
Section: Discussionsupporting
confidence: 86%
“…We compared the performance of our model with two different models from the literature - Peng et al [24] and Yin et al [25]. The Peng et al model was originally trained on data from UK Biobank T1ws, whereas the Yin et al model was originally trained on ADNI T1ws.…”
Section: Resultsmentioning
confidence: 99%
“…Preventing BCL11A from binding to the DNA would be a preferred therapeutic route, however directly competing with DNA using a small molecule seems overly challenging. One plausible route is to find antibodies or nanobodies 28 binding BCL11A and inducing protein degradation (PROTAC approach). Alternatively, small molecules could achieve the same results or stabilize the apo conformation of BCL11A preventing it from binding to DNA.…”
Section: Discussionmentioning
confidence: 99%